PENGARUH ETIKA DAN KOMPENSASI TERHADAP KINERJA APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DI INSPEKTORAT KABUPATEN TULUNGAGUNG - Anam, Huda Khoirul; Satyawan, Made Dudy (COMPETITIVE, 2024)
This study aims to prove effect of ethic and compensation on the performance of the Government’s Internal Supervision Apparatus (APIP) in the Inspekctor of Tulungagung district. The reseacrhers interested to study performance APIP as dependent variabel, while of ethic and compensation use for independent variables. Of the 31 respondents used in this study are apips. Data retrieval is made through a direct distribution of the questionnaire to the responders. The inputs measure a likert range 1 scale (strongly disagrees) to 10 strongly agree to a variety of answers. Testing mechanisms include msi testing for interval data to ordinal, test of data quality, test of classic assumptions, linear regression berganda analysis using a version 23 SPSS device used for processing research data showing that ethics and compensation have a positive effect on the performance of the apip government inter-government surveillance apparatus (apip) in the inspector of tulunggreat district, With a percentage of influence of 49.7% while 50.3% is affected by other variables.